Human error analysis in the staff of the metal control room industry by CREAM Cognitive Approach - Yaser Lotfi; Hamid Hobobati; Gholamhossein Halvani; Ali Sadri; Raziyeh Soltani; Masoud Rostami; Vida Anoosheh (طب کار, 2025)
Introduction: The CREAM method is a technique for estimating human error and conducting reliability analyses, which can be utilized to assess the level of control over operator errors in the workplace. Materials & Methods: The present study was a descriptive-analytic case study. The Analytic Hierarchy Process (HTA) was first applied to eamine the job duties, and subsequently, using finding from the original CREAM method, the control approach for the production header, the senior control operator, tactical control, and control operator, and the operator at the real-ime control site were calculated. Results: The results obtained from the original CREAM approach indicated that the control style for the production headquarter tasks, the senior operator of the control, tactical control and the site control operator employed the instantaneous type. For the analysis of  the four jobs, the most frequently errors pertained to runtime, interpretation, planning, and visual errors, respectively. Conclusion: According to the expectations, the task of senior control and production header is a controlling type and in two other cases, parameters such as concurrent work, time of work performance and quality of training have caused instantaneous control. Finally, the primary cognitive error for the four analyzed tasks pertains to the "runtime error", while the key cognitive function linked to the control process in the control room is the action of "communication".